REVEALING THE REASONS FOR THE IMPLEMENTATION OF PKB AND BBNKB OPTIONS TO INCREASE REGIONAL TAXES - Riska Putri Herwanda; Marta Cindy Aulia; Aurellia Christa Febyandhani; Mohamad Djasuli (Politeknik Negeri Ambon, 2025)
Introduction: One of the sources of regional revenue comes from the Motor Vehicle Tax (PKB) and the Motor Vehicle Name Return Fee (BBNKB). However, with the change in regulations, the Regional Government enforces the option. Option is an additional tax levy according to a certain percentage that serves to increase the potential of regional revenue. The implementation of options depends on public understanding and adequate infrastructure support. The purpose of this study is to reveal the reasons for the implementation of the PKB and BBNKB options and their relationship with the increase in regional taxes. Methods: This research uses a qualitative method, which uses several sources such as statutory regulations and related scientific articles. Results: This research adds a new perspective to previous research which only focused on the potential revenue of Regency/City local governments through the Opsen PKB scheme without revealing the reasons for implementing Opsen PKB and BBNKB. For this reason, in this research, the author will reveal the reasons for implementing Opsen PKB and BBNKB. Keywords: BBNKB, Option; Regional Taxes; PKB